HOW IS SOCIAL MEDIA USED BY INDONESIAN SCHOOL PRINCIPALS FOR INSTRUCTIONAL LEADERSHIP? - Lantip Diat Prasojo; Lia Yuliana (Jurnal Cakrawala Pendidikan, 2021)
Information technology and communication adoption, including social media, remains an interesting research theme in this digital era, especially in a developing country like Indonesia. A survey of principals’ perceptions in Indonesia on the factors that influence the use of social media for instructional leadership serves as the focus of this study. Using a sequential approach, 122 principals responded to the questionnaire which adapted the Technology Acceptance Model (TAM) containing six constructs namely perceived ease of use, perceived usefulness, perceived attitude, perceived facilitating conditions, subjective norm, and behavioral intention to use technology; and seven of them were interviewed to give further explanations on their perception. The different test was used on for the results of the interview for the quantitative data analysis and thematic analysis. This research finds that the principals’ use of the social media in instructional leadership is considered satisfactory. There is no significant difference regarding the use of social media for instructional leadership based on sex or age, but there is a significant difference based on age in which principals aged more than 50 years have the highest average of TAM. From the interviews, it can be concluded that principals use social media for work to make communication more effective and efficient. The use of social media between the principal and teaching staff proves to be a great way for communication and supervision, not only to report on the teaching and learning process, but also other activities such as administrative reports and financial discussions.